Predicting Movie Success at the Box Office - Gunter, Barrie. author. aut Link
VII, 270 p.
Keywords: This book explores the different factors that can influence a new movie’s prospects at the box office. Looking at factors such as the production budget, distribution model, genre, stars and audience reactions of films, Gunter asks how such aspects may reduce the uncertainties of success so common in the movie industry. The reader is taken on a journey through filmmaking factors that, research suggests, impact box office performance. While box office revenues represent only part of a movie’s earning potential, Gunter highlights how theatrical performances remain central to what the movie business is about. The chapters illustrate how ticket sales are largely influenced by the production budget but also cultural differences and new movie platforms. .